Laser aerosol time-of-flight mass spectrometry analysis of individual aerosol particles from photooxidation of toluene - Huang, Ming-Qiang; Wang, Zhen-Ya; Hao, Li-Qing; Zhou, Liu-Zhu; Gu, Xue-Jun; Fang, Li; Zhang, Wei-Jun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A laser aerosol time-of-flight mass spectrometry (ATOFMS) that can be used for real-time measurement of the size and composition of individual aerosol particles has been designed and manufactured in our laboratory. Particles are introduced into the instrument through a particle beam interface, sized by measuring the delay time between two scattering lasers, and compositionally analyzed using a laser desorption/ionization linear-time-of-flight mass spectrometry. Secondary organic aerosol particles from the photooxidation of toluene in the CH3ONO/NO/air mixture were generated in a home-made smog chamber and measured using it. Experimental results showed that the individual aerosol particles from photooxidation of toluene can be measured in real-time by this instrument. This unique capability is impossible in off-line methods such as chromatography and chemical method.
Optica Applicata, Vol. 36, 2006, nr 1, s. 5-13
Keywords: optyka; secondary organic aerosol (SOA); laser desorption/ionization; laser aerosol time-of-flight mass spectrometer (ATOFMS)